Interfacial microstructure and strengthening mechanism of dissimilar laser al/steel joint via a porous high entropy alloy coating - Zheng, Min (2023)
Publisher Copyright: © 2023 The Authors This work was supported by the National Natural Science Foundation of China (No. 52275155) and Class III Peak Discipline of Shanghai-Materials Science and Engineering. JPO acknowledges funding by national funds from FCT-Fundacao para a Ciencia e a Tecnologia, I.P., in the scope of the projects LA/P/0037/2020, UIDP/50025/2020 and UIDB/50025/2020 of the Associate Laboratory Institute of Nanostructures, Nano-modelling and Nanofabrication-i3N.